STATE OF PARENTS’ MEDICAL KNOWLEDGE AND THEIR MOTIVATION FOR PREVENTION OF ARTERIAL HYPERTENSION AMONG CHILDREN - Мехтієва, А.Ф. (World of Medicine and Biology, 2016)
A survey of mothers of three groups of schoolchildren with arterial hypertension (AH), high-normal blood pressure and control group was carried out. The results show that inadequate medical awareness, a variety of sources of information parents, primarily mothers, leads to late diagnosis among schoolchildren AH, even in the presence of her debut symptoms. Also reduced the level of their commitment to fulfilling children medical prescriptions of doctors. In this regard, it is necessary to conduct mass outreach to inform parents about measures to protect the health of schoolchildren, including the prevention of hypertension among them.